Strategi Pengembangan Pendidikan Agama Islam Berbasis Digital di Daerah Tertinggal: Digital-based Islamic Religious Education Development Strategy in Disadvantaged Areas - Yadri, Emil; Ratna Sari, Serli (CV. Kalimasada Group, 2023)
The development of educational strategies is not as fast as technological developments. The existence of digitalization in all segments of life demands the digitalization of education and science. Today's digital-based education system has become a necessity. However, this cannot necessarily be applied in all places, such as in underdeveloped areas. Where everything goes slowly. This is motivated by attitudes, culture and social values ​​that are inherent in society which tends to still hold traditional values. It is very necessary to develop Islamic religious education in underdeveloped areas based on digital technology in order to improve the quality and equality of national education. Apart from that, this development is also intended to offset the negative influence of the digital world which has damaged the world of primary and secondary education. In order to realize this development, strategies are needed that can be accepted and adopted well by people living in disadvantaged areas. The strategy must comply with the local values ​​where the development is carried out. Coordination with related parties from the socialization process to implementation is also part of the strategy that must be implemented.